2016
DOI: 10.1002/wps.20346
|View full text |Cite
|
Sign up to set email alerts
|

How effective are cognitive behavior therapies for major depression and anxiety disorders? A meta‐analytic update of the evidence

Abstract: We report the current best estimate of the effects of cognitive behavior therapy (CBT) in the treatment of major depression (MDD), generalized anxiety disorder (GAD), panic disorder (PAD) and social anxiety disorder (SAD), taking into account publication bias, the quality of trials, and the influence of waiting list control groups on the outcomes. In our meta-analyses, we included randomized trials comparing CBT with a control condition (waiting list, care-as-usual or pill placebo) in the acute treatment of MD… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

11
349
3
3

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 422 publications
(379 citation statements)
references
References 197 publications
11
349
3
3
Order By: Relevance
“…Since the 1970s, several hundreds of randomized trials have shown that these interventions are effective [11][12][13][14] , although their effects are modest and have been overestimated because of the low quality of many trials 15 and publication bias 16,17 . The effects of psychotherapies have been found to be comparable to those of pharmacotherapy 18 , and probably last longer 19 .…”
mentioning
confidence: 99%
“…Since the 1970s, several hundreds of randomized trials have shown that these interventions are effective [11][12][13][14] , although their effects are modest and have been overestimated because of the low quality of many trials 15 and publication bias 16,17 . The effects of psychotherapies have been found to be comparable to those of pharmacotherapy 18 , and probably last longer 19 .…”
mentioning
confidence: 99%
“…In their response, they did not provide any evidence for either the poor(er) quality of studies of PDT for anxiety, nor for superiority of CBT. A recent meta-analysis by Cuijpers et al 2 found that more than 80% of CBT trials in anxiety disorders used waiting-list control groups, a weak comparator. Only 17% (21 of 121)…”
Section: Science Not Propaganda Is What We Need In the Treatment Ofmentioning
confidence: 99%
“…2 This led these authors to conclude that CBT is only "probably effective" in anxiety disorders, and that "because of the small number of high-quality trials, these effects are still uncertain and should be considered with caution". 2 Note the marked difference in conclusion by a group of authors that includes major proponents of CBT. Furthermore, recent meta-analyses have found PDT to be as efficacious as CBT in anxiety disorders 3 and across mental disorders.…”
Section: Science Not Propaganda Is What We Need In the Treatment Ofmentioning
confidence: 99%
“…CBT is a therapeutic approach consisting of numerous models using a broad set of techniques targeting different psychiatric (Cuijpers, Cristea, Karyotaki, Reijnders, & Huibers, 2016) and somatic (Ljótsson et al, 2013) disorders. Within the scope of cognitive interventions there are computerised tasks such as ABM.…”
Section: Cognitive-behavioural Interventionsmentioning
confidence: 99%